A response to the design-oriented information systems research memorandum - Baskerville, Richard; Lyytinen, K.; Sambamurthy, V.; Straub, D. (Palgrave Macmillan Ltd., 2011)
In response to Österle et al.'s' Memorandum on Design Oriented Information Systems Research', this commentary disputes, and expands the context of, several premises used to justify the main argument in the memorandum. These include: (1) claims about the evolution and role of design science research in the broader IS community and its position in the so-called 'Anglo-Saxon community', (2) the journal reviewing standards applied to design science research and what is perceived to be a sole focus on behavioral 'descriptive' research in certain IS journals. This commentary also discusses how such journals operate and set up their missions, review principles, and standards.